Effectiveness of Benson’s Relaxation Technique on perceived stress and pain among patients undergoing hemodialysis in Amman, Jordan - Abu Maloh, Haya Ibrahim Ali (2023)
Jordanian hemodialysis patients are required to dedicate four hours to every hemodialysis session, three times per week. The long-term hemodialysis treatment increases their perceived stress and pain levels. Jordanian hemodialysis patients lack coping strategies to manage their perceived stress and pain in clinical practice. There was no intervention utilized in hemodialysis units for reducing perceived stress and pain among Jordanian hemodialysis patients. This study aimed to evaluate the effectiveness of Benson’s Relaxation Technique in reducing perceived stress and pain among hemodialysis patients at governmental hospitals in Amman, Jordan. A clusterrandomized, active-control trial was conducted in two large governmental hospitals in Amman, Jordan that were randomly assigned to intervention and active-control hospitals. A total of 132 hemodialysis patients were selected randomly, and data were collected over four data collection periods using the Perceived Stress Scale (PSS-10) and the Short-Form McGill Pain Questionnaire (SF-MPQ). The intervention group received a training session of Benson’s Relaxation Technique and they were asked to perform it twice a day for 10 minutes over eight weeks. Both descriptive and inferential statistics were conducted (mean, standard deviation, frequencies, chi-squared, independent t-tests, one-way analysis of variance, Pearson correlation coefficient, and mixed between-within subject analysis of variance). The study results revealed that most hemodialysis patients were male (54.5%), had a mean age (years) of (38.06 ± 11.247), were unmarried (44.7%), had a mean length of time on hemodialysis (years) of (7.11 ± 3.898), and held a high school qualification (35.6%). All hemodialysis patients had dialysis three times per week for a total of four hours per session. The total perceived stress mean score was (30.70 ± 4.237), the total pain rating index mean score was (32.56 ± 4.202) and the total visual analogue scale mean score was (7.53 ± 1.251). Many patients (43.9%) described their present pain intensity as ‘distressing’ and the lower extremities were the most commonly reported location of pain (38.6%). The participants’ ages (years) and lengths of time on hemodialysis (years) were strongly positively correlated with their perceived stress and pain levels. Findings indicated a non-statistically significant reduction in the perceived stress and pain scores between pre-intervention and post-intervention at two weeks (P>0.05). However, a statistically significant reduction was noted in the perceived stress and pain scores of the intervention and active-control groups between: preintervention and post-intervention at one month (P<0.001); pre-intervention and postintervention at two months (P<0.001); post-intervention at two weeks and postintervention at one month (P<0.001); post-intervention at two weeks and postintervention at two months (P<0.001); and post-intervention at one month and postintervention at two months (P<0.001). Based on the findings, Benson’s Relaxation Technique is a beneficial and cost-effective technique that enables significant reductions in perceived stress and pain among hemodialysis patients, but not after two weeks of performing the technique. Performing Benson’s Relaxation Technique for at least one month led to a significant reduction in perceived stress and pain among hemodialysis patients. Therefore, the implementation of Benson’s Relaxation Technique at hemodialysis units is likely to help hemodialysis patients reduce their perceived stress and pain.